A Lightweight Deep Learning Framework using Resource-Efficient Batch Normalization for Sarcasm Detection - Jiby Mariya Jose,; Jeeva Jose, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Communication is not always direct; it often involves nuanced elements like humor, irony, and sarcasm. This study introduces a novel two-level approach for sarcasm detection, leveraging Convolutional Neural Networks (CNNs). Convolutional neural networks (CNNs) are crucial for many deep learning applications, yet their deployment on IoT devices is challenged by resource constraints and the need for low latency, particularly in on-device training. Traditional methods of deploying large CNN models on these devices often lead to suboptimal performance and increased energy consumption. To address this, our paper proposes an energy- efficient CNN design by optimising batch normalisation operations. Batch normalisation is vital for deep learning, aiding in faster convergence and stabilising gradient flow, but there has been limited research on creating energy-efficient and lightweight CNNs with optimised batch normalisation. This study proposes a 3R (reduce, reuse, recycle) optimisation technique for batch normalization. This technique introduces an energy-efficient CNN architecture. We investigate the use of batch normalization optimization to streamline memory usage and computational complexity, aiming to uphold or improve model performance on CPU- based systems. Additionally, we evaluate its effectiveness across diverse datasets, focusing on energy efficiency and adaptability in different settings. Furthermore, we analyze how batch normalization influences the performance and effectiveness of activation functions and pooling layers in neural network designs. Our results highlight batch normalization’s ability to enhance computational efficiency, particularly on devices with limited resources.
Keywords: Lightweight Convolutional Neural Networks (CNN); Lightweight Diabetic Retinopathy Detection; Lightweight Mineral Classification; Batch Normalisation (BN); Edge devices; Energy Efficiency